Forced Marriage in Cultural Practices and Sexual Violence Law - Saputra, Sarping; Putri, Ririn Maulina; Fahmia Syihab, Syifa Maulida (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2023)
This study analyzes criminal law policy regarding forced Marriage disguised as a cultural practice, taking into account current conditions and the legal protection provided by Law Number 12 of 2022 concerning Criminal Law of Sexual Violence (TPKS).  This is a problem in itself, considering that several regions in Indonesia still embrace the culture of forced Marriage. At the same time, on the other hand, many parties say that it violates human rights, while many cultural practices then derogate many human rights.  Then how does the TPKS Law see forced Marriage, which in some regions is legalized by customary laws? To answer this, this study uses a normative legal research methodology through a statutory approach. The collection of legal materials will involve an examination of relevant regulations, which will then be analyzed comprehensively to arrive at conclusions that answer the research questions. This study find that (1) policies regarding forced marriages conducted under the guise of culture have been regulated in the TPKS, thus changing actions that were previously not considered criminal offenses into criminal offenses that can be subject to legal sanctions. (2) Legal protection against forced Marriage under the guise of culture is divided into two forms of protection, namely preventive protection carried out by the central and regional governments and repressive protection in the form of imposing sanctions on perpetrators, accompanied by various additional sanctions and providing rights for victims during the judicial process and afterward.